Artesunate monotherapy versus artesunate plus quinine combination therapy for treatment of imported severe malaria: a TropNet retrospective cohort study - Botta, Annarita; Comelli, Agnese; Vellere, Iacopo; Chechi, Flavia; Bianchi, Leila; Giulia, Gardini; Tomasoni, Lina Rachele; Spinicci, Michele; Galli, Luisa; Castelli, Francesco; Bartoloni, Alessandro; Zammarchi, Lorenzo (Infection, 2022)
Background The addition of intravenous quinine (IVQ) to intravenous artesunate (IVA) has been recently suggested by World Health Organization  in areas where artemisinin resistance is highly prevalent. Since IVA is not yet widely available as “Good Manufacturing Practices” product, for several years combination treatment with IVA and IVQ was used in some Italian centers to mitigate the legal risks in using an unlicensed drug. Methods A retrospective cohort study was designed to compare IVA + IVQ and IVA treatment for imported severe malaria. We collected data from three Italian centers. Adult and pediatric cohorts were analyzed separately. Results Forty-nine patients treated with IVA and 44 with IVA + IVQ were enrolled, 45 were adults and 48 children. All acquired malaria in Sub-Saharan Africa. In the adult cohort, median of fever clearance time (FCT) was similar in both groups (48 h vs 48 h, p = 0.19) but number of patients who reached apyrexia within 48 h (FCT48) was higher in IVA group (20/24, 83.3% vs 8/17, 47%, p = 0.002). The parasite clearance time (PCT) measure did not differ (median 48 h vs 48 h, p = 0.669). In the pediatric cohort, FCT did not differ in the two groups (median 30 vs 48 h, p = 0.50) while PCT was longer in IVA + IVQ group (median 72 vs 48 h, p = 0.002). Adverse events (AEs) in adults were more common in the combination treatment group (6/19, 31.58% vs 2/26, 7.69%, p = 0.055). Conclusion IVA + IVQ treatment did not show better outcome with respect to IVA monotherapy. AEs were more frequent in the IVA + IVQ group compared to the monotherapy. Further studies are necessary to investigate whether IVA + IVQ could be an efficient strategy to treat severe malaria cases in areas at high risk of artemisinin resistance.